2004
DOI: 10.3758/bf03194864
|View full text |Cite
|
Sign up to set email alerts
|

Immediate spatial distortions of pointing movements induced by visual landmarks

Abstract: We tested the influence of two horizontally aligned visual landmarks on pointing movements to memorized targets, to investigate whether the visuomotor system can make use of an egocentric representation unaffected by visual context. The endpoints of pointing movements were systematically distorted toward the nearest visual landmark, indicating that spatial representations included both target and nontarget information. These distortions were not due to the presence of the landmarks during the movement but, rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 45 publications
(77 reference statements)
5
52
3
Order By: Relevance
“…Previous studies of immediate recall of single spatial locations suggest that when local landmarks are visible, locations are encoded in relation to these landmarks, even though egocentric encoding is still possible (see, e.g., Diedrichsen et al, 2004;Lemay et al, 2004). Since in the present study the visual environment was visible at all times, we might expect egocentric encoding to have made little contribution to spatial span.…”
Section: Summary and Interpretation Of Resultscontrasting
confidence: 42%
See 2 more Smart Citations
“…Previous studies of immediate recall of single spatial locations suggest that when local landmarks are visible, locations are encoded in relation to these landmarks, even though egocentric encoding is still possible (see, e.g., Diedrichsen et al, 2004;Lemay et al, 2004). Since in the present study the visual environment was visible at all times, we might expect egocentric encoding to have made little contribution to spatial span.…”
Section: Summary and Interpretation Of Resultscontrasting
confidence: 42%
“…After a short interval, participants had to indicate the position of the target (1) in total darkness (so that target location could be encoded only egocentrically), or (2) with respect to a local visible landmark that was stationary (permitting either egocentric or allocentric encoding), or (3) with respect to a landmark that was moved between presentation and test (permitting only allocentric encoding). In at least two recent studies, the pattern of pointing errors was markedly different for the egocentric versus the allocentric conditions; when either reference frame was available, the pointing errors indicated a preference for allocentric encoding (see, e.g., Diedrichsen, Werner, Schmidt, & Trommershauser, 2004;Lemay, Bertram, & Stelmach, 2004). These results suggest that proximal spatial position is coded with respect to a landmark, if one is available, rather than with respect to the observer's position.…”
Section: Short-term Memory For Single Locationsmentioning
confidence: 71%
See 1 more Smart Citation
“…If not extinguished at the right time, this allocentric cue could influence the behavioral response. For example, reach tends to be biased toward the nearest irrelevant landmark (Diedrichsen et al 2004). This could affect numerous studies, so we will highlight just one relevant example.…”
Section: Comparison To Previous Cue-combination Studiesmentioning
confidence: 99%
“…Spatial reference frames were inferred from the pattern of pointing errors, which depended on the arrangement of stimuli at presentation and conditions at the time of response. For example, Diedrichsen, Werner, Schmidt, and Trommershäuser (2004) reported that the pattern of pointing errors made to briefly presented and masked dots was influenced by the presence of landmark stimuli in the otherwise blank field. Similar error patterns were found when observers were required to encode position with respect to landmarks that moved between presentation and recall, consistent with (but not necessarily implying) allocentric coding.…”
Section: Discussionmentioning
confidence: 99%